Investigations on wheelchair seating pressure relief system for pressure ulcer prevention among paraplegics / Norhani Md Nadzri - Norhani, Md Nadzri (2021)
Individuals with paraplegia spend their time in a wheelchair for life. Adapting to prolonged wheelchair seating for almost all activities of daily living is challenging. The loss of abilities to sense any pain or excessive seating pressure cause them to remain seated on the wheelchair without any pressure relief activities. This situation leads to secondary complications including pressure ulcers which further degrades the individualï¿½s health. A wheelchair seating pressure relief training system (WSETs) was developed to overcome this. Optimal placement of the force sensitive resistors (FSR) as seating pressure sensors on the cushion was determined, and their responses were investigated with 5 people with paraplegia. Two different FSR orientations, A and B, were compared. Each paraplegic sat in a resting position and then performed pressure relief activities (PRA) which included whole body push-up, left and right lean and forward lean, before returning to resting position. With more forward positioned FSRs, Orientation B showed higher sensitivity, implying better capture of the high-risk areas of pressure ulcer development. The FSR sensor readings were significantly different among pressure relief activities in all subjects (p<0.05), indicating the validity of FSR measures for the intended application. In conclusion, the WSETs system was proven suitable as a training tool for new paraplegics to habituate themselves in performing PRA.